Czy "identyfikacje teoretyczne" są koniecznymi prawdami aposteriorycznymi? - Odrowąż-Sypniewska, Joanna (Filozofia Nauki, 2006)
As it is well known, Kripke has argued that theoretical identifications (such as „Water is H2O”, „Cats are animals”, „Heat is the motion of molecules”) are statements which if true are examples of the necessary a posteriori. In this paper we will show that all these claims can be challenged. First of all, not all of the statements that Kripke mentions are identity statements. Second, Kripke justifies their necessity by arguing that they contain rigid designators. The problem is that the notion of rigid designation has not been defined by him for general terms and it is not obvious how it should be defined. Moreover, it seems that even if we assume that the terms „water” and „H2O” are rigid, their rigidity does not suffice to establish that the statement „Water is H2O” is necessary. Third, it might be argued that „Water is H2O” is not even true, because the claim that water is H2O leads to the claim that water vapor is H2O and snow is H2O, which in turn leads to the absurd conclusion that snow is water vapor. Fifth, terms such as „water” are indeterminate and the precise borders of their extensions have to be fixed by stipulation, which casts some doubt upon the claim that statements such as „Water is H2O” are a posteriori.